The Effect of Implementing Green Accounting and Environmental Perfomance on Return on Assets (ROA) in the Non-Cyclical Consumer Sector Listed on the Indonesian Stock Exchange - Eneng Winda Widanengsih; Maria Lusiana Yulianti (DINASTI RESEARCH, 2022)
This study aims to examine the effect of implementing green accounting and environmental performance on the company's Return on Assets. The population in this study are manufacturing companies in the Consumer NON Cyclical sector listed on the Indonesia Stock Exchange in 2017-2021. Samples were selected using a purposive method sampling with the specified criteria resulted in 8 companies that were worthy of observation, with a research period of 5 years (2017-2021) so that a total of 40 research samples were obtained. This research uses multiple regression analysis using SPSS program. In this study, green accounting variables are measured using the dummy method, environmental performance variables are measured using PROPER rating values ??and variable Profitability with Return on Assets. Based on the analysis results show that the green variable accounting influences and influences Return on Assets. While Environmental Performance has no effect on Return on Assets.